Determination of Ground Subsidence by Sentinel-1 SAR Data (2018-2020) over Binh Duong Quarries, Vietnam - Long, Nguyen Quoc; Van Anh, Tran; Khac Luyen, Bui (VNU Journal of Science: Earth and Environmental Sciences, 2021)
Mining-induced subsidence is often determined by field survey methods, e.g., using total station or global navigation satellite system (GNSS) technology. The advantage of these methods is high accuracy, but they are usually employed in a small-scale areas. Radar technology has been developed and applied to determine surface subsidence over a large area at a few millimeters accuracy. In this paper, 24 Sentinel-1B SAR images are used with the Permanent Scatter Interferometry (PSInSAR) method to determine the land subsidence of the Tan My-Thuong Tan quarries and surrounding areas in Binh Duong province, Vietnam. The results are compared with the average annual subsidence of 20 GNSS surveying points from January 2018 to March 2020. The correlation coefficient of annual average land subsidence of the two methods is bigger than 0.8, indicating the feasibility of applying the InSAR Sentinel-1 data processed by the PSInSAR method to determine the mining-induced subsidence of ground surfaces over quarries and surrounding areas.